Comparative Test on the Level Contamination of Escherichia coli and Salmonella sp. on Broiler Meat at Slaughterhouses and Traditional Markets in Medan - Manurung, K.A; M. Tafsin; P. Patriani; M. Simbolon (Talenta Publisher, 2023)
Contamination of meat is common Contamination of meat often occurs which endangers the health of consumers. This study aims to determine the presence of bacterial contamination of Escherichia coli and Salmonella sp. on broiler meat at slaughterhouses and traditional markets in Medan City. This study used a survey method with a purposive sampling technique and used 60 samples (30 from slaughterhouses and 30 from traditional markets). There were 3 slaughterhouses (slaughterhouses Johor, slaughterhouses setia budi, and slaughterhouses padang bulan) and three traditional markets (traditional market Johor, Setia Budi and Padang bulan). Samples were analyzed at the Laboratory Microbiology Faculty of Mathematic and Natural Science Universitas Sumatera Utara Medan. The results showed that the average total amount of Escherichia coli in the sample from chicken slaughterhouses was 3.15 log CFU/g, and from the traditional markets was 3.39 log CFU/g. The number of samples contaminated by Salmonella sp. in chicken slaughterhouses was 17 of 30 samples, whereas on the traditional market were 20 of the 30 samples. This study concludes that the average total amount of Escherichia coli microbes in samples from chicken slaughterhouses and traditional markets in Medan City all of them had exceeded the maximum limit of microbial contamination, based on the microbiological quality requirements of SNI 3932: 2008, which is 1x101 CFU/g. While the bacterial contamination rate of Salmonella sp. in chicken slaughterhouses was 56%, and in the traditional market was 66%.